Cultures and Disasters: Understanding Cultural Framings in Disaster Risk Reduction - Krüger, Fred; Bankoff, Greg; Cannon, Terry; Orlowski, Benedikt Marko; Schipper, Lisa (Routledge, 2015)
Why did the people of the Zambesi Delta, affected by severe flooding, return early to their homes or even choose to not evacuate? How is the forced resettlement of small-scale farmers living along the foothills of an active volcano in the Philippines impacting on their day-to-day livelihood routines? Making sense of such questions and observations is only possible by understanding how the decision making of societies at risk is embedded in culture, and how intervention measures acknowledge, or neglect, cultural settings. The social construction of risk is being given increasing priority in the understanding of how people experience and prioritise hazards in their own lives and how vulnerability can be reduced, and resilience increased, at a local level. Cultures and Disasters adopts an interdisciplinary approach to explore the cultural dimension of disaster with contributions from leading international experts in the field. Section I provides a discussion of research in both theoretical and practical considerations to better understand the importance of culture in hazards and disaster management. Culture can be interpreted widely with many different perspectives; this enables us to critically consider the culturally-bound nature of research itself as well as the complexities of incorporating various interpretations into Disaster Risk Reduction (DRR). If culture is omitted from consideration, related issues of adaptation, coping, intervention, knowledge and power relations cannot be fully grasped. Section II explores what aspects of culture shape resilience and how people use culture in everyday life to establish DRR practice. It looks at what constitutes a resilient culture and what role culture plays in a society’s decision making. It is natural for people to seek refuge in tried and trusted methods of disaster mitigation; however, cultural and belief systems are constantly evolving. How these coping strategies can be introduced into DRR therefore poses a challenging question. Finally, Section III examines the effectiveness of key scientific frameworks for understanding the role of culture in DRR and management. DRR includes a range of norms, and breaking these through improved cultural understanding will challenge established theoretical and empirical frameworks.

Die Grounded Theory in der Geographie. Ein möglicher Weg zu Empirie und Theoriebildung nach dem Cultural Turn - Geiselhart, Klaus; Park, Martina; Orlowski, Benedikt Marko; Schlatter, Fabian (Berichte zur Deutschen Landeskunde, 2012)
Apparently, epistemological realism has been largely overcome in the course of the cultural turn. Yet the essential problem of dualism between theory and practice remains. Grounded Theory research directly aims at this problem. Nevertheless, this research style has not yet been incorporated substantially into the academic field of Human Geography, although it is more popular in other social sciences. Especially for Geography which is a deeply empirical discipline there is a necessity for reflected and integrated methodologies. In this article we will outline the basic concepts of Grounded Theory Methodology. Based on these outlines we will point out some problems researchers might face, but also show benefits and implications. We argue that the Grounded Theory Methodology can be one important way of bridging the gap between theory and practice and that it can give an additional value to geographic research after the Cultural Turn.

E-Partizipation als neuer Impuls in stadtplanerischen Prozessen? Von den Visionen der Stadtplanenden zu den Utopien der BürgerInnen. - Franz, Katrin; Haidl, Isabela; Hartmann, Kerstin; Lehnhoff, Felix; Riedmann, Sofrony; Bittner, Christian; Orlowski, Benedikt Marko (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2014)
Keywords: E-Partizipation; E-Government; Stadtplanung

Kulturgeographisches Geländepraktikum – Leitfaden. Erlanger Skripte zum Geographiestudium - Gebauer, Matthias; Geiselhart, Klaus; Fürmaier, Peter; Haferburg, Christoph; Kaplan, Lena; Kieslinger, Julia; Kordel, Stefan; Kress, Martina; Lendl, Jonas; Orlowski, Benedikt Marko; Pohle, Perdita; Schnorr, Kristina; et al. (2015)

Maß und Messbarkeit von Alltag. Alltag zwischen Transformation und Kontinuität in der Erwerbslosigkeit - Orlowski, Benedikt Marko (2010)
Folgt man den Ansichten klassischer und aktueller Studien zu den sozialen Implikationen von  Erwerbslosigkeit und betrachtet dem gegenüber den öffentlichen DIskurs zur Thematik Arbeitslosigkeit, so ergibt sich offenbar ein schwieriges Spannungsfeld mit dem Menschen in der Arbeitslosigkeit konfrontiert sind: Während langanhaltende Arbeitslosigkeit eine reale Bedrohung für die ökonomische, soziale und gesundheitliche Lebensqualität darstellt, setzt die „Faulenzerdebatte“ mit ihren diskriminierenden Zügen unter sozialen Druck. In der Arbeit beschäftigt sich der Autor aus einer sozialgeographischen Perspektive mit diesem Spannungsfeld und jenen Menschen, die mit ihm tagtäglich konfrontiert sind. Die Studie verfolgt das Ziel, Erwerbslosigkeit als eine besondere „Krisensituation des Alltags“ genauer zu beschreiben und zu verstehen. Dabei wird der Frage nachgegangen, was „Alltag“ eigentlich genau bedeutet (auch im Sinne einer Geographischen Perspektive) und wie sich Erwerbslosigkeit auf den Bezug von Mensch, Alltag und Raum auswirkt. Die empirische Untersuchung zu dieser Arbeit soll daher einen Einblick in die konkrete Lebensrealität einer – wie sich zeigen wird – besonders benachteiligten Gruppe erwerbsloser Personen geben: „Ältere“ Menschen ohne Arbeit.
Keywords: Arbeitslosigkeit; Langzeitarbeitslosigkeit; Erwerbslosigkeit; Alltag; Raum; Zeitgeographie; Aktionsraumsforschung; Tagebücher

Pfade des Konsumentenverhaltens. Der Konsument jenseits gängiger Typologien - Geiselhart, Klaus; Orlowski, Benedikt Marko (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2013)
Konsum ist ein zentraler Ausdruck zeitgenössischer Gesellschaften. Konsum bestimmt nicht nur den gesellschaftlichen Status sondern bietet auch eine wichtige Orientierung für Selbst- und Gruppenidentitäten. Während gängige Konsumententypologien Konsumenten in festgeschriebene Charaktere kategorisieren, beschreibt dieser Artikel sie in ihrer Flexibilität und Veränderlichkeit. In diesem Sinne ist diese Studie eine Kritik kommerzieller Konsumentenforschung. Konsumenten haben die Fähigkeit über Ihre Intentionen zu reflektieren und können ihr Konsumentenverhalten beeinflussen. Das Konsumentenverhalten des Einzelnen wird dargestellt in seiner chronologischen Abfolge einzelner Kaufakte. Der „Verhaltensraum des Konsumenten“ wird als abstrakter Raum mit zwei Freiheitsgraden entwickelt. Diese Dimensionen sind das Ergebnis theoretischer überlegungen und wurden empirisch evaluiert. Das Verhalten der Konsumenten wird als Pfade in diesem abstrakten Raum dargestellt. Schließlich werden auch noch Orte des Konsums in diesem Raum kartier
Keywords: Konsum; consumer style

Rivalling Disaster Experiences. The Case of the Seismo-Volcanic Crisis of El Hierro, Canary Islands - Orlowski, Benedikt Marko (Transcript, 2021)
People experience disasters very differently. Conflicts about a »correct« interpretation of the risks might arise. The side-by-side of different truths lead to people seeing mismanagement and disinformation. The volcanic crisis of El Hierro shows how rivalling interpretations amongst affected islanders, the media, sciences, and disaster response institutions cause great social tensions and scepticism towards scientific information. Thus, to fully understand disaster risk, the focus must shift to the rifts between established convictions and the individuals' creativity to overcome them, taking into account their embeddedness in various fields of practice, each with their own rationales and rupture
Keywords: Disasters; Culture; Media; Crisis; Risk; Disaster Mitigation; Disaster Risk Reduction (DRR); Nature; Human; Civil Society; Cultural Geography; Human Ecology; Environmental Policy; Geography

Staging a disaster and restaging a ‘community’ – the seismic crisis of El Hierro - Orlowski, Benedikt Marko (AAG Anual Meeting 2015, 2015)
Small islands and their communities appear to be a perfect laboratory for disaster risk studies: clear-cut, isolated, manageable and consistent. But what if a disaster reveals that the idea of an island 'community' is a metaphor rather than a coherent entity and, in addition, a 'disaster' is staged rather than real? In 2011, El Hierro (Canary Islands) experienced a volcanic crisis. An offshore, submarine eruption caused colouring of the sea, the emission of gas and floating volcanic bombs. The situation triggered a partly dramatized media coverage. This 'staging' has an effect on islanders' risk perceptions, since it differs from their own interpretation of events. As framing El Hierro as a hazardous place has damaged the islanders' well-being, coping strategies have aimed at altering how the seismic event has been represented. Local media are managing their reporting carefully and authorities omit statements about possible risks. A closer look at the range of experiences reveals that the crisis people lived through was actually the interaction of rivalling 'framings' of the natural event. To counter the crisis, long-established framings are mobilized and, thus, the significance of the community is increased: Being Herreño means being connected to nature, neglected by those in power and, consequently, a member of a resilient and strong community. As this identity is very compatible with current circumstances, where the fight against adversity is highlighted, statements from individuals in regard to volcanic risk often return to it. This 'restaging' of the community both has important implications for adaptation and preparedness.

The cultural sense of disasters: Practices and singularities in the context of HIV/AIDS - Geiselhart, Klaus; Schlatter, Fabian; Orlowski, Benedikt Marko; Krüger, Fred (Cultures and Disasters: Understanding Cultural Framings in Disaster Risk Reduction, 2015)
Defining a disaster is a cultural act: naming a disaster first starts with recognising societal conditions that are evaluated to be disastrous. Plainly, this can only be done in reference to values and norms. In a second stage, conditions tagged as disastrous become traced to either a hazardous event or to social circumstances and dealings that have reduced people’s resilience, rendered them vulnerable, or hampered their appropriate response to threats. It is thus intelligible that in different cultures, depending on particular perceptions and values, disasters can be substantially different things. Disaster definitions, for example, are created by organisations, institutions or individuals with regard to their own practical assignments. But, then, how can ‘a culture’ be identified, a situation be narrowed down to a ‘disaster’, and appropriate disaster risk reduction (DRR) measures be initiated?
Keywords: Risk; Disaster; Culture